2012
DOI: 10.5455/vetworld.2012.742-747
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism - A cause for dilated cardiomyopathy in dogs; four year study 2008-2011

Abstract: Aim : The study was carried out to understand the thyroid dysfunction and its association with dilated cardiomyopathy in dogs. Materials and Methods: The study was done at Teaching Veterinary Hospital, Bhoiguda, College of Veterinary Science, Hyderabad for four years, i.e., from 2008 to 2011. A total of 256 dogs of various breed, age and sex were presented with typical skin and coat abnormalities. Few were also exhibiting signs of low metabolic rate. Skin sample analysis was done to rule out the causes of der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…There was reduced contractility of chambers manifested by low EF% (30.11±3.23%) and FS% (13.43 ±1.62%). Present findings were in agreement with earlier studies Karlapudi et al (2012)…”
Section: Resultssupporting
confidence: 94%
“…There was reduced contractility of chambers manifested by low EF% (30.11±3.23%) and FS% (13.43 ±1.62%). Present findings were in agreement with earlier studies Karlapudi et al (2012)…”
Section: Resultssupporting
confidence: 94%
“…These conditions can contribute to an enlarged left atrium and ventricle and can resemble a DCM phenotype ( Saunders and Gordon, 2015 ). The FDA Vet-LIRN report also stated 9% ( n = 18) had concurrent hypothyroidism, which has been known to increase the risk of cardiovascular disease ( Karlapudi et al, 2012 ). Lastly, 8% ( n = 17) of the dogs had a concurrent diagnosis of tick-borne diseases, such as Lyme or Anaplasmosis.…”
Section: Limitations To Current Fda Reportsmentioning
confidence: 99%
“…Historically, dilated cardiomyopathy ( DCM ) has been considered to be primarily an inherited disease, with higher prevalence in specific dog breeds ( Dukes-McEwan et al, 2003 ; Sammarco, 2008 ). However, other causes of DCM include specific nutrient deficiencies ( Freeman et al, 2001 ; Backus et al, 2003 ) and concurrent diseases, such as endocrine ( Karlapudi et al, 2012 ; Janus et al, 2014 ), myocarditis, and chronic tachycardia ( Calvert et al, 1997 ). Recently, there has been concern regarding the relationship of diets with specific characteristics, such as, but not limited to, grain-free diets and those containing legumes, novel protein diets, and those produced by small manufacturers to DCM in dogs ( Freeman et al, 2018 ); however, no definitive link has been established at this time.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of hypothyroidism as a metabolic aetiology for secondary cardiomyopathy was also described as another possible causative factor in the development of DCM (Karlapudi et al 2012). However, in Doberman Pinchers, the role of hypothyroidism in the aetiology or progression of DCM was not confirmed (Beier et al 2015).…”
mentioning
confidence: 99%
“…It has been suggested that hypothyroidism can play a role in the development of DCM in dogs. In some studies, the therapy of hypothyroidism led to an increased fraction shortening and ejection fraction of the left ventricle (Tidholm et al 2001;Karlapudi et al 2012).…”
mentioning
confidence: 99%